Treatment and Partner Notification Outcomes for Clients Diagnosed With Chlamydia and Gonorrhea Through GetCheckedOnline Compared With Sexually Transmitted Infection Clinics in British Columbia, Canada. Issue 2 (11th February 2023) - Zamanpour, Arina; Grennan, Troy; Ablona, Aidan; Fairley, Christopher K.; Estcourt, Claudia; Mema, Silvina; Hoyano, Dee; Ogilvie, Gina; Wong, Jason; Gilbert, Mark
Abstract : A study comparing treatment and partner notification outcomes for people diagnosed with chlamydia or gonorrhea found no differences between clients of Internet-based and clinic-based testing services. Abstract : Background: Whether treatment, engagement in partner notification (PN), and PN outcomes differ between clients of Internet-based and clinic-based testing services is poorly understood. We compared these outcomes between people diagnosed with chlamydia and/or gonorrhea (CT/GC) through a sexually transmitted infection (STI) clinic service and GetCheckedOnline (GCO), an Internet-based testing service in British Columbia. Methods: We conducted a retrospective matched cohort study among CT/GC cases where each case diagnosed through GCO in 2016 to 2017 was matched to 2 STI clinic cases by diagnosis, sex, age group, and specimen collection date. Data were collected through chart review, with outcomes compared using appropriate statistical tests. Results: Of 257 GCO and 514 matched clinic cases, case treatment was high and did not differ between GCO (254 of 257 [98.9%]) and clinic (513 of 514 [99.8%]) cases, as was engagement in PN (250 of 257 [97.2%] vs. 496 of 514 [96.5%]). There was no difference in the proportion of notified partners between GCO (159 of 270 [58.9%]) and clinic (253 of 435 [58.2%]) cases, although a greater proportion of partners reported by clinic cases were notified by STI nurses (43 of 435 [9.9%]) versus GCO cases (6 of 270 [2.2%]). Conclusions: GetCheckedOnline clients diagnosed with CT/GC demonstrated similar treatment uptake and engagement in PN to clinic clients, and PN outcomes did not differ. The greater reliance on STI clinic nurses for PN among clinic clients may be related to having had an initial in-person testing visit.